PHOTOSTABILITY OF BACTERIOCHLOROPHYLL a AND ITS DERIVATIVES AS POTENTIAL SENSITIZERS FOR PHOTODYNAMIC CANCER THERAPY: THE STUDY ON ACETONE-WATER AND METHANOL-WATER SOLVENTS - Leenawaty Limantara; Heriyanto Heriyanto (Universitas Gadjah Mada, 2011)
The determination of photostability for Mg-BChl a, Zn-BPheo a and Cu-BPheo a irradiated with red light (≥ 630 nm, 870 lux) and equilibrated with air for 20 min in acetone-water and methanol-water solvents at various percentages of water has been done. The presence of light and oxygen in the pigment solution cause the pigment instable. The pigment stability toward photooxidation is extremely influenced by solvent properties, including oxidation potential value and solvent abilities to form coordination and aggregate. Degradation products of pigment during irradiation treatment can be detected by increment of absorption at the absorption spectrum or occurrence of new positive absorption bands at the different absorption spectra. Cu-BPheo a is a promising photosensitizer based on its stability toward photooxidation in acetone-water solvents.